2008
DOI: 10.1038/sj.bjc.6604408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment with epoetin-β on survival, tumour progression and thromboembolic events in patients with cancer: an updated meta-analysis of 12 randomised controlled studies including 2301 patients

Abstract: Epoetin-b is used to treat patients with metastatic cancer undergoing chemotherapy to alleviate the symptoms of anaemia, reduce the risk of blood transfusions and improve quality of life. This meta-analysis of 12 randomised, controlled studies evaluated the impact of epoetin-b on overall survival, tumour progression and thromboembolic events (TEEs). A total of 2297 patients were included in the analysis (epoetin-b, n ¼ 1244; control, n ¼ 1053; 65% solid and 35% nonmyeloid haematological malignancies). A prespe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 35 publications
(46 reference statements)
1
51
1
1
Order By: Relevance
“…ECOG performance status (PS) was considered as a dichotomous variable (> 2 or ≤ 2), since there was not always enough clinical information available in the charts to classify patients with a PS ≤ 2 further. Medication use thought to be associated with a higher risk of VTE was also abstracted and included: erythropoietin stimulating agents (ESA) [13], estrogen and progestin containing medications [14], tamoxifen [15] and bevacizumab [16]. Overall survival follow-up was complete for all patients.…”
Section: Methodsmentioning
confidence: 99%
“…ECOG performance status (PS) was considered as a dichotomous variable (> 2 or ≤ 2), since there was not always enough clinical information available in the charts to classify patients with a PS ≤ 2 further. Medication use thought to be associated with a higher risk of VTE was also abstracted and included: erythropoietin stimulating agents (ESA) [13], estrogen and progestin containing medications [14], tamoxifen [15] and bevacizumab [16]. Overall survival follow-up was complete for all patients.…”
Section: Methodsmentioning
confidence: 99%
“…In the four studies with longterm follow-up data, when all events were included, median follow up was also comparable (28.8 months with epoetin-b and 29.8 months with control) (Aapro et al, 2008a). …”
Section: Baseline Characteristics and Follow-upmentioning
confidence: 99%
“…Baseline characteristics of the patients in the analysis are described in the earlier publication (Aapro et al, 2008a) and are shown in Table 2. Of the 2297 patients in the analysis, 35% had non-myeloid haematological malignancies (mainly non-Hodgkin's lymphoma or multiple myeloma) and 65% had solid tumours (most commonly primary malignancies of the breast, head and neck, colon/rectum and ovary).…”
Section: Baseline Characteristics and Follow-upmentioning
confidence: 99%
See 2 more Smart Citations